Olfactory dysfunction and altered cortical excitability in the mouse model of Fragile X Syndrome - Felipe Arancibia; Marcelo Rojas; Diego Becerra; Rocío Fuenzalida; Christian Cea-Del Rio; Jorge Mpodozis; Magdalena Sanhueza; Alexia Nunez-Parra (Biological Research)
Abstract Fragile X Syndrome (FXS) is the most common monogenetic cause of autism and inherited intellectual disability. A key feature of FXS symptomatology is altered sensory processing greatly affecting FXS individual’s life quality. Here, we use a combination of behavioral tests and slice physiology tools to study the neurophysiological alterations underlying aberrant sensory processing in the olfactory system of the FXS mouse model (Fmr1 KO). We focused on the piriform cortex (PC), since it is in this brain region where olfactory information is integrated and ultimately decoded. Using a go-no go behavioral task we have found that Fmr1 KO learn to discriminate between a rewarded and a not rewarded odorant but cannot distinguish complex odor mixtures, akin to what is found in the environment. Moreover, Fmr1 KO long-term memory is impaired compared to control mice suggesting possibly cortical processing alterations. In addition, electrophysiological data from PC layer II neurons of Fmr1 KO mice showed a hyperexcitable phenotype manifested by differences in active membrane properties and altered network connectivity. Taken together, our data suggest a possible causal link between the observed olfactory discrimination deficiencies in the Fmr1 KO mouse and the altered physiology of PC.